How Digital Inclusion Can Help Solve Grand Challenges - Yokoi, Tomoko; Yokoi, Tomoko; Obwegeser, Nikolaus; Beretta, Michela (MIT Sloan Management Review, 2021)
When hackathons are held virtually, people from a variety of circumstances have an opportunity to participate. But facilitating such events entirely online requires an organizational and mindset shift for making the collaboration work, with greater emphasis on steps such as onboarding and building in fun. Recent hackathons around COVID-19 offer insights into how to make remote collaboration succeed with participants who have diverse backgrounds, perspectives, and experience with technology.